X+4/3x-2=1

Simple and best practice solution for X+4/3x-2=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+4/3x-2=1 equation:



X+4/3X-2=1
We move all terms to the left:
X+4/3X-2-(1)=0
Domain of the equation: 3X!=0
X!=0/3
X!=0
X∈R
We add all the numbers together, and all the variables
X+4/3X-3=0
We multiply all the terms by the denominator
X*3X-3*3X+4=0
Wy multiply elements
3X^2-9X+4=0
a = 3; b = -9; c = +4;
Δ = b2-4ac
Δ = -92-4·3·4
Δ = 33
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-\sqrt{33}}{2*3}=\frac{9-\sqrt{33}}{6} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+\sqrt{33}}{2*3}=\frac{9+\sqrt{33}}{6} $

See similar equations:

| 75-2y=50 | | 3y+24y=5y | | (x+8)^2-2=47 | | 1/3x(12x-6)=4x-9 | | -2(v+6)=-8v+18 | | -t+6=20-3t | | 1/5(x-2/3)=7/15 | | 1/x+6=1 | | 1/2(x+8)=1/4x-6 | | 4-2x=5(x-2) | | 4x+4=6x+24 | | 12t-10=14 | | 8-4x=-19 | | 10/x+6=5/4 | | 4(4-4n)=9n | | X+2/2=x+7 | | -2(x-2)=2-4x+8 | | (2+5v)=3v+14 | | s-$10=$20.67 | | 2x+2/6=-5 | | x3=−3431331 | | n/4=n+5/10 | | 80.8=8(m+3.9) | | -6b-24=-2b+6(4b-4) | | 11.1-7.7n=3.9-7.8n+6.8 | | -4.9t2+30.5t+9.9=0 | | 14=64-2x^2 | | (D²+5D-3)y=6 | | 7(4w+2)/5=7 | | b36=59 | | 12(1x-5)=11(x+5) | | -8n=1 |

Equations solver categories